Student's perception of integrating TED Talks to promote speaking fluency: A case study - Anugrah Kirana, Sandra; Laila Sulistyani, Ummi Nur (ELT Forum: Journal of English Language Teaching, 2025)
This article explores how an English Department student perceives using TED Talks to develop speaking fluency in English in English as a Foreign Language (EFL) contexts. Although speaking fluency is one of the most essential and visible aspects of communicative competence, it remains one of the most challenging skills to master due to limited exposure to authentic input and low confidence among learners. TED Talks offer authentic, multimodal resources with engaging and culturally diverse styles of fluent English speech. Drawing on theories of perception, multimedia learning, and speaking pedagogy, this article categorizes the discussion into one main objective: how student's perception about TED Talks as a tool to enhance speaking fluency. The findings from this research and the reviewed previous studies suggest that students generally perceive TED Talks positively. The participant admires the fluency, organization, and delivery style of various TED Talks speakers and feels inspired to emulate them. Repeated exposure to TED Talks contributed to vocabulary enrichment, greater pronunciation, and increased motivation in learning. In conclusion, TED Talks might not be a one-size-fits-all solution, but they hold a promising source that can be thoughtfully integrated into a speaking learning activity.